Essential-oil pesticidal odorscapes: An exploratory multi-endpoint framework for profiling plant volatiles against walnut-associated stored-product beetles - Gabriel Omar Denett; Maria Rosa Rodriguez; Virginia L. Usseglio; Daniela Milagros Bracamonte; Tamara Elizabeth López; Jose Francisco Aranda Cano; María Paula Zunino; Jorge Omar Werdin Gonzalez; Diego Alejandro Sampietro; Nieves Carolina Comelli (Journal of Stored Products Research, 2027)

Dry-fractionated Amylaceous pea flour for phosphate reduction in mortadella: Technological, oxidative and sensory impacts during refrigerated storage - Géssica Hollweg; Jaqueline Graziela de Oliveira Zuchetto; Andressa Inês Schú; Bibiana Alves dos Santos; Maximiliano Segundo Escalona Jiménez; Matheus Abraão Piovesan Pedroso; Alexandre José Cichoski; Jose Manuel Lorenzo Rodriguez; Viviani Ruffo de Oliveira; Paulo Cezar Bastianello Campagnol (Meat Science, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

A comprehensive assessment of different approaches for medium spatial resolution land surface phenology using in situ leaf observations across Mediterranean and Atlantic broadleaf ecosystems - Jose A. Caparros-Santiago; Victor Rodriguez-Galiano (Advances in Space Research, 2026)

Beyond Coverage: A Systematic Review and Thematic Analysis of Delivery, Compliance, Equity and Impact in Mass Deworming for Soil-Transmitted Helminths - Harley M. Rodriguez; Angelica Marie B. Rostata; Jan Joseph Rainer Christorey Maria Salgado; Timothy Liam D. Rivera; Jose Ma. M. Angeles (Acta Parasitologica, 2026)

Towards a European small-scale fishing vessel tracking programme: Overview, challenges and opportunities - Tania Mendo; Anna Mujal-Colilles; Einar Hjorleifsson; Pamela Lattanzi; Luca Marsaglia; Mark James; Marta M. Rufino; Helen Holah; Oliver Tully; Jose Rodriguez-Gutierrez; Patrik Jonsson; Estanis Mugerza; et al. (Marine Policy, 2026)

A GIS–AHP Framework for Sustainable Well Placement: Application for Natural Gas and Hydrogen Exploration in the Eastern Cordillera Basin, Colombia - Salim A. Salon; Sebastian S. Rodriguez; Jhon M. Muñoz-Barrera; Fabián Gallego; Cesar Mora; Deysi P. Forero; Jose F. Osorno; Cristian Peñafort (Natural Resources Research, 2026)

Age at menarche and exposure to non-persistent pesticides in Spanish girls from the INMA (environment and childhood) project - Carmen Freire; Alicia Olivas-Martinez; Francesca Castiello; Alba Jimeno-Romero; Sara Lopez de Calle; Beatriz Suárez; Adonina Tardón; Marta M. Rodriguez-Suarez; Mònica Guxens; Martine Vrijheid; Andrea Beneito; Maria-Jose Lopez-Espinosa (Environmental Research, 2026)

Optimism predicts future economic mobility among hurricane maria migrants - Maria Duque; Yara Acaf; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Pablo Montero-Zamora; Evelyn Gualdron; Mia Cisco; Sumeyra Sahbaz; Carolina Scaramutti-Gladfelter; Lawrence G. Watkins; Duyen H. Vo; Seo Woo Lee; et al. (Climate and Development, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

The impact of climate-induced extreme weather events on soil constraints and ecosystem functioning - Manish Kumar; Shiv Bolan; Anandkumar Naorem; Smirti Shukla; Nitika Chandel; Santanu Mukherjee; Cherukumalli Srinivasa Rao; Patricia Saco; Jose Rodriguez; Karolina Furtak; Renu Dhupper; Sasha Jenkins; et al. (Journal of Soils and Sediments, 2026)

Mechanical Performance of Thoracic Aortic Stent-Grafts: An In Vitro and In Silico Study - Anna Ramella; Sara Barati; Giulia De Campo; Giulia Luraghi; Jose Felix Rodriguez Matas; Frederic Heim; Nabil Chakfé; Tim J. Mandigers; Irene Fulgheri; Maurizio Domanin; Santi Trimarchi; Francesco Migliavacca (Annals of Biomedical Engineering, 2026)
Thoracic endovascular aortic repair (TEVAR) is the standard of care for thoracic aortic pathologies, and its clinical success is related to the choice of stent-grafts (SGs). In this study, we conducted a comprehensive assessment of four commercial SGs (Valiant Captivia (VC), Terumo RelayPro Bare Stent (TBS), Cook Zenith Alpha (CZA), and Gore CTAG (CTAG)) to evaluate their mechanical performance in idealised and patient-specific conditions. High-fidelity finite element models were developed and validated against experimental tests and in vitro TEVAR procedures in 3D-printed rigid phantoms. The validation showed strong agreement between simulations and experiments (average error Then, the SGs were virtually deployed in two aortic models to investigate device-wall interaction through geometrical and mechanical parameters. A greater metal density led to increased graft apposition (up to 94%) and increased radial forces (up to 354 N vs 116N). Conversely, sparser metal structures produced lower but more localised stress regions: maximum values of 0.25 MPa versus 0.49 MPa with denser metal. Higher stresses may contribute to improved device fixation and, when associated with greater apposition, may reduce the risk of endoleak. Nevertheless, high stresses could potentially induce long-term vascular remodelling. These results underscore the influence of SG’s design on TEVAR outcomes and support the integration of validated computational simulations into pre-operative planning. The SG performance varied across patient anatomies: this study highlights the importance of personalized device selection and establishes a foundation for using in silico methods to optimize TEVAR strategies and mitigate procedural risks.

Effects of Fishmeal Substitution with House Cricket Meal (Acheta domesticus) on Productive Performance and Nutrient Metabolism of Blue Tilapia (Oreochromis aureus) - Aldo Fraijo-Valenzuela; Joe Luis Arias-Moscoso; Francisco Cadena-Cadena; Barbara Aboites-Martínez; Ramón Casillas-Hernández; Libia Zulema Rodriguez-Anaya; Pablo Gortáres-Moroyoqui; Jose Reyes Gonzalez-Galaviz (Fishes, 2026)
A 10-week feeding experiment was conducted to evaluate the effects of replacing fishmeal with cricket meal on the productive performance and transcriptional responses of genes related to nutrient metabolism and growth of blue tilapia (Oreochromis aureus). Five conventional tilapia feeds were formulated to replace fishmeal with cricket meal. Control diet (CD) was formulated with 20% fishmeal, and four diets gradually replaced fishmeal with cricket meal at 20, 40, 60, and 80% (D1–D4). A total of 200 fingerling tilapia (2.00 ± 0.09 g) were randomly distributed into 20 tanks (10 fish/tank), with four replicates per dietary treatment. The results showed that fish fed CD and D1 had higher growth performance values than those fed D2–D4. The feed conversion ratio (FCR) was significantly better in fish fed CD and D1 compared with fish fed D2–D4. The survival rate was similar for all treatments. The transcriptional response of genes related to nutrient digestion, absorption, and transport; lipid metabolism; and the somatotropic axis was marked downregulated in fish fed D2 and D4, whereas in fish fed D3, it exhibited a unique compensatory regulation across most pathways, likely sustained by its higher dietary lipid content. Although cricket meal did not prevent the metabolic effects associated with high soybean meal inclusion, survival remained high across all treatments. Cricket meal can replace up to 20% of the fishmeal in the feed for blue tilapia fingerlings, with soybean meal as the main protein source.

The Effect Of Localized Circumferential Residual Stress On Pressurized Stress State Of CT Reconstructed Vessels: A Finite Element Study - Vittorio Lissoni; Martina Schembri; Giulia Luraghi; Alessandro Caimi; Virginia Fregona; Mauro Di Giancamillo; Jessica Bassi; Ferdinando Auricchio; Michele Conti; Gabriele Dubini; Francesco Migliavacca; Jose Felix Rodriguez Matas (Annals of Biomedical Engineering, 2026)
Purpose Residual stresses are intrinsic stresses present in arteries even in the absence of external loads or blood pressure. They originate during growth and remodeling and contribute to vascular mechanical equilibrium. Despite advances in computational methods, incorporating residual stresses into patient-specific vascular models remains challenging. Evidence regarding the influence of circumferential residual stresses on physiological loading in realistic anatomies is still limited. Methods We combined in vitro imaging, mechanical testing, and finite element (FE) simulations to incorporate residual stresses into a pressurized porcine aorta model. Medical images were acquired in both pressurized and zero-stress states, the latter obtained after 2 h of longitudinal cutting. Locally measured mechanical properties from distinct aortic regions were used to define an orthotropic hyperelastic material response. Residual stresses were restored by simulating vessel closure under displacement-controlled boundary conditions with a tied contact interface. Stress distributions were then compared in FE pressurization simulations performed with and without residual stresses. Results Residual stresses substantially influenced the predicted stress fields. They homogenized stress across the vessel thickness and reduced stress concentrations near the lumen. Moreover, lumen cross-sectional areas at 120 mmHg aligned more closely with experimental measurements when residual stresses were included. In contrast, neglecting residual stresses produced an average overestimation of lumen area by 4.84% and stress peaks up to 50% higher in the inner wall. Conclusion This study highlights the importance of accounting for residual stresses in biomechanical vascular simulations. Incorporating them improves prediction accuracy and reduces artificial stress concentrations, which is crucial for patient-specific risk assessment and surgical planning.

Impact of volcanic emissions on the air quality during the 2021 volcanic eruption of Tajogaite, La Palma: Implications for population exposure to volcanic pollutants - Julia Eychenne; Raphael Paris; Agnès Borbon; David Jessop; Mathieu Gouhier; Guillem Gisbert Pinto; Antoni Calafat; Aurélie Colomb; José-Luis Fernandez-Turiel; Vincent Gaussen; Clara Gorce; Séverine Moune; et al. (Science of The Total Environment, 2026)

Clinical image analysis to build patient-specific models of acute ischemic stroke patients - Virginia Fregona; Ilaria Bottini; Sara Barati; Amedeo Cervo; Antonio Macera; Ghil Schwarz; Guglielmo Pero; Mariangela Piano; Gabriele Dubini; Jose Felix Rodriguez Matas; Giulia Luraghi; Francesco Migliavacca (Physical and Engineering Sciences in Medicine, 2026)
Mechanical thrombectomy (MT) is an emergency treatment for acute ischemic stroke (AIS) to remove a clot occluding a large cerebral vessel. Histological analysis on retrieved thrombi have shown that they are mainly composed of red blood cells (RBCs), platelets and fibrin, and the outcome of MT appears to be influenced by clot composition. Therefore, being able to predict clot composition from routine medical images used for AIS diagnosis could support the choice of interventional strategy. Along with that, finite element simulations of the MT procedure can help provide insights into the impact of the procedural choices, the vessels morphology and the clot characteristics on the MT outcome. To achieve this, a realistic representation of the involved structures is necessary. In this context, this work aimed to (i) develop a methodology for the analysis of routine radiological images aiming at inferring information about clot characteristics (position, length, and composition) and (ii) develop a semi-automatic pipeline to position the clot in the patient-specific reconstructed geometry to build a patient-specific model which could be the starting point for the in silico replica of the MT procedure. However, image analysis alone could not distinguish between white and mixed clots, while a distinction between red and non-red clots was possible. Consequently, histological analyses were used to assign the clot composition, and thus the mechanical properties, in the positioning simulation. The resulting patient-specific model showed a strong similarity with pre-interventional clinical images.

Hydrologic connectivity as a predictor of degradation thresholds across semiarid sites with different vegetation patterns - Samira Azadi; Patricia M. Saco; Mariano Moreno-de las Heras; Jose F. Rodriguez (CATENA, 2026)

Quantifying Time-Lagged Vegetation Responses to Hydroclimatic Factors in Dam-Influenced Arid Regions Using VAR Modeling and Remote Sensing - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (Environmental Management, 2026)

Nanoplastics internalization impairs mitochondrial activity in equine sperm - Sofia Dindo; Laura Tovar-Pascual; Vito Antonio Baldassarro; Diego Bucci; Beatrice Mislei; Marcella Spinaci; Jose Manuel Ortiz-Rodriguez (Theriogenology, 2026)

Molecular responses to pollution stress in glass eels (Anguilla anguilla): Gene expression changes associated with varying contamination levels and temperature across estuaries - Alvaro Gutierrez-Rodriguez; Claudia Nuñez-Moyano; Lucía Rivas-Iglesias; Susana Acle; Luis Jose Royo-Martin; Eva Garcia-Vazquez; Gonzalo Machado-Schiaffino (Aquatic Toxicology, 2026)

Phytochemicals as promising agents against pathogenic free-living amoebas - Erick P. Gutiérrez-Grijalva; Laura A. Contreras-Angulo; Marilyn Shomara Criollo-Mendoza; J. Basilio Heredia; Jaime López-Cervantes; Dalia Isabel Sánchez-Machado; Jose Reyes Gonzalez-Galaviz; Libia Zulema Rodriguez-Anaya (Phytochemistry Reviews, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Genetic diversity of Mycoplasma bovis isolated from bovine respiratory disease and bovine mastitis in Chile - Matías Goddard; Joscelyn San Martín; Jose Arturo Molina-Mora; Luis Collado; Jaime Rodriguez; Nicolás Galarce; Armin Mella (Veterinary Microbiology, 2025)

Effect of polystyrene nanoplastics on in vitro maturation of pig cumulus-encosed oocytes - Marcella Spinaci; Sofia Dindo; Nadia Govoni; Laura Tovar; Alessandro Marino Volsa; Cinzia Cappannari; Diego Bucci; Jose Manuel Ortiz-Rodriguez (Research in Veterinary Science, 2025)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

Integrated photovoltaic system for rainwater collection and sustainable irrigation - Antonio García-Chica; Angel Mariano Rodriguez-Perez; Julio Jose Caparros-Mancera; Cesar Antonio Rodríguez-Gonzalez; Rosa Maria Chica (Irrigation Science, 2025)
The integration of photovoltaic systems with rainwater harvesting offers a promising solution for enhancing water and energy management in arid and semiarid agricultural regions."This study presents an agrivoltaic system where photovoltaic panels function both as energy source and as surfaces for runoff collection, directing rainwater into a storage reservoir for irrigation. A detailed analysis was conducted to evaluate different scenarios, for a period of ten years, including panel inclination, optimizing at 35°, and the expansion of the photovoltaic field, to enhance energy efficiency and water availability. The results demonstrate that this approach significantly reduces water shortages, reducing critical cases below 50% in first scenario, particularly during peak irrigation demand periods, while increasing the system’s storage capacity and overall resilience to climate variability. The expansion of the photovoltaic system, which is scalable according to the application, demonstrates the overall reduction of critical cases in irrigation availability, increasing the reservoir capacity up to 60,000 m3, which can be combined with increased management of energy generated for the grid, or local generation in remote areas, in combination with improved water supply management. Additionally, the system improves energy sustainability by reducing reliance on external sources and lowering carbon emissions from agricultural activities. The findings highlight the potential of integrating photovoltaic systems into irrigation management as a scalable and replicable framework for enhancing resource efficiency and sustainability in water-scarce regions.

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

A review of different removal techniques for pesticides found in European waters identified by the European Environmental Agency - James Disley; Guzman Gil-Ramirez; Jose Gonzalez-Rodriguez (Environmental Science & Policy, 2025)

Mechanisms and Therapeutic Potential of Key Anti-inflammatory Metabiotics: Trans-Vaccenic Acid, Indole-3-Lactic Acid, Thiamine, and Butyric Acid - Muñoz-Olivos Cristina; Bautista-Rodriguez Elizabeth; Rivas-Arreola María Jose; Palacios-Gonzalez Berenice; Zacapa Diego; Cortez-Sanchez Jose Luis (Probiotics and Antimicrobial Proteins, 2025)

Paragonimiasis in Southeast Asia: A 60-Year Bibliometric Analysis (1963–2023) - Harley M. Rodriguez; Jose Ma. M. Angeles (Acta Parasitologica, 2025)

A bioactive soluble recombinant mouse LIGHT promotes effective tumor immune cell infiltration delaying tumor growth - Maria-Luisa del Rio; Oscar-Mariano Nuero-Garcia; Giovanna Roncador; Raquel Garcimartín-Bailon; Juan-Carlos Cubria; Pascal Schneider; Jose-Ignacio Rodriguez-Barbosa (Journal of Molecular Medicine, 2025)
The TNF family member LIGHT (TNFSF14) binds to two receptors, HVEM (TNFSFR14) and LTβR (TNFSFR3). HVEM functions as a costimulatory molecule, whereas LTβR is involved in the development of lymph nodes and ectopic tertiary lymphoid structures at chronic inflammation sites. The classical approach of fusing soluble recombinant proteins to the Fc fragment of IgG resulted in a functionally inactive Ig.mouse (m) LIGHT protein. However, in line with the fact that TNF family members cluster receptors as trimers, addition of a small homotrimeric domain (foldon) N-terminal of mLIGHT produced an Ig.Foldon-mLIGHT protein able to bind and engage HVEM and LTβR in a cell-based reporter bioassay. In the tumor model of B16.F10 melanoma cells implanted into syngeneic recipients, cells transduced with membrane-bound mLIGHT grew as aggressively as mock-transduced cells, but growth of tumors of B16.F10 cells expressing Ig.Foldon-mLIGHT was delayed and characterized by significant immune infiltration of dendritic cells and cytotoxic cells. This work unveils the potential of active soluble LIGHT, as a single agent, to recruit cytotoxic cells and dendritic cells at the tumor site to inhibit tumor growth. This effect may be further enhanced with immune checkpoint blockade therapies. Key messages The classical approach of fusing soluble recombinant proteins to the Fc fragment of IgG resulted in a functionally inactive Ig.mouse (m) LIGHT (TNFSF14) protein. The addition of a small homotrimeric domain (foldon) N-terminal of mouse LIGHT produces a proper folded bioactive mouse LIGHT recombinant protein. Constitutive intratumor expression of secreted Ig-Foldon-LIGHT, but not membrane LIGHT, delays tumor growth. Tumors secreting LIGHT, as a single agent, promote beneficial anti-tumor responses through the recruitment and infiltration of cytotoxic cells and dendritic cells. Graphical Abstract The intrinsic source of native soluble LIGHT and LTα1β2 (produced by neutrophils and activated T cells and NK cells) along with the tumor secreting recombinant Ig.Foldon-LIGHT co-stimulate NK and T cells through HVEM and license DC for antigen presentation to promote anti-tumor T cell responses in the tumor draining lymph nodes. Furthermore, native LIGHT produced by neutrophils, NK, and T cells and recombinant LIGHT along with LTα1β2 secreted by recruited B cells (LTi, lymphoid tissue inducer cells) would together activate stromal cells of the tumor microenvironment (TME) through LTβR (LTo, lymphoid tissue organizing cells) to release chemokines driving endothelial activation and the upregulation of adhesion molecules that in turn would facilitate transmigration of immune cells from the blood vessels to the tumor site. It would also condition myeloid cells expressing LTβR to secrete cytokines such as TGF-beta that contribute to blood vessel normalization.

Mitochondrial bioenergetics analysis on SLC-selected boar spermatozoa during liquid storage - Estibaliz Lacalle; Beatrice Mislei; Cristina Algieri; Marcella Spinaci; Felipe Martinez Pastor; Salvatore Nesci; Jane M. Morrell; Jose M. Ortiz-Rodriguez; Diego Bucci (Animal Reproduction Science, 2025)

Amino acid and acylcarnitine profile of Aedes aegypti (L) post-blood feeding, after permethrin exposure, and during the life cycle - Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodriguez; María de Lourdes Ramírez-Ahuja; Olga Karina Villanueva-Segura; Patricio Adrián Zapata-Morin; Griffith Samuel Lizarraga; Laura E. Martinez-de-Villarreal; Margarita L. Martinez-Fierro; Ivan Delgado-Enciso; Jose Ignacio Gonzalez-Rojas; Adriana E. Flores; Antonio Guzman-Velasco; et al. (Insect Biochemistry and Molecular Biology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Mush system heterogeneities control magma composition and eruptive style on the Ocean Island of El Hierro, Canary Islands - Claudia Prieto-Torrell; Helena Albert; Meritxell Aulinas; Eloi González-Esvertit; Ilenia Arienzo; Guillem Gisbert; Valentin R. Troll; Jose-Luis Fernandez-Turiel; Alejandro Rodriguez-Gonzalez; Francisco-Jose Perez-Torrado (Contributions to Mineralogy and Petrology, 2025)
The study of recent eruptions in Ocean Islands (OIs) provides a unique window into the magma dynamics governing their plumbing systems and the mechanisms leading to eruptions. Here we present an integrated approach to unravel the dynamics of magmatic plumbing systems through detailed spatial, petrological, and geochemical characterisation of volcanic products ranging from crystal-rich ankaramitic lavas to trachytic tephras. We focus on the textural and geochemical spatial variations of 42 Holocene subaerial eruptions at the OI of El Hierro (Canary Islands), as well as on their petrogenetic significance for magmatic evolution and plumbing system architecture. Integrating geochemical data within fractional crystallisation modelling and mass balance calculations reveals that ankaramitic and porphyritic lavas with phenocryst modal abundances > 10 vol% result from melt extraction and crystal accumulation. Aphyric to sub-aphyric eruption products and porphyritic lavas with phenocryst modal abundances < 10 vol% usually follow fractional crystallisation trajectories that start at ~ 10 wt% MgO. Periodic extraction of evolved melt from crystal mushes likely led to the occurrence of minor trachytic eruptions, which are difficult to reconcile with simple closed system fractional crystallisation trends. A complex, heterogeneous crustal mush system beneath El Hierro is, in fact, the most reliable scenario to explain the wide range of textures, whole-rock and mineral compositions, and the overall surface distribution of vents and eruptive styles displayed by the Holocene volcanism on the island. Our integrated findings highlight the importance of a combined field, petrological, and geochemical study to decipher plumbing system dynamics of OI magmatism. The results allow us to put forward an updated conceptual model of the current plumbing architecture of El Hierro’s volcanic system during the Holocene.

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Corrigendum to “Sustainable proteins from wine industrial by-product: Ultrasound-assisted extraction, fractionation, and characterization” [Food Chemistry 455 (2024) 139743] - Samuel Rodriguez Garcia; Jose C. Orellana-Palacios; David Julian McClements; Andres Moreno; Yoana Rabanal-Ruiz; Milad Hadidi (Food Chemistry, 2025)

Exploring Construction and Demolition Waste as a Sustainable Adsorbent for Efficient Removal of AB113 Dye from Aqueous Solutions - Brahim Arhoun; Maria del Mar Cerrillo-Gonzalez; Maria Villen-Guzman; Juan Manuel Paz-Garcia; Jose Miguel Rodriguez-Maroto (Water, Air, & Soil Pollution, 2025)
An innovative approach to the treatment of textile wastewater by utilizing fine fractions of construction and demolition waste (CDW) as a cost-effective adsorbent is presented in this work. Through batch experiments, the impact of key parameters on the adsorption process was explored, identifying optimal conditions: natural pH, adsorbent dosage (S/L) of 20 g L −1 , and temperature of 20 °C. The characterization of CDW was performed using ICP, BET, FTIR, SEM–EDX, XPS, and XRD. The kinetics of adsorption were effectively described by the Elovich model, while equilibrium adsorption data showed good agreement with the Freundlich model. The maximum monolayer adsorption capacity for acid blue AB113 dye on CDW obtained from Langmuir isotherm was 89.52 mg g –1 . Thermodynamic analysis indicated an exothermic and feasible nature of the adsorption process. The results of this study highlight the potential use of fine CDW as a promising adsorbent to remove acid blue113 dye from textile wastewater. Graphical Abstract

Sources, levels, and determinants of indoor air pollutants in Europe: A systematic review - Carla Martins; Vânia Teófilo; Marta Clemente; Mariana Corda; Jose Fermoso; Alicia Aguado; Sandra Rodriguez; Hanns Moshammer; Alexandra Kristian; Mireia Ferri; Belén Costa-Ruiz; Leticia Pérez; et al. (Science of The Total Environment, 2025)

SAmMD: The South American mineral deposit database - Guilherme Ferreira da Silva; Martín Ricardo Gozalvez; Alonso Arturo Marchena; Anderson Dourado Rodrigues da Silva; Braulio Ignacio Aguila Aravena; Diego Jesús Rodriguez; Eduardo Linares; Edwin Fernando Gallardo Vargas; Franco Drausin Pinzon Rivas; Guillermo Lopez Aguilera; Jose Amado Rondon Muñoz; Juan Manuel Turra; et al. (Journal of South American Earth Sciences, 2025)

Understanding Environmental Factors Influencing Vegetation Cover Downstream of Dams - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (International Journal of Environmental Research, 2025)

Assessing the impact of the new Mexico cable car on air pollution - Juan Prieto-Rodriguez; Jose Ignacio Azuela-Flores; Daniel Groft; Maria Jose Perez-Villadoniga; Rafael Salas (Journal of Transport Geography, 2025)

The diurnal variation of dust and water ice aerosol optical depth at Jezero crater observed by MEDA/TIRS over a full Martian year - Michael D. Smith; Germán M. Martínez; Eduardo Sebastián; Mark T. Lemmon; Samuel A. Atwood; Daniel Toledo; Daniel Viúdez-Moreiras; Aurélien Stcherbinine; Jose Antonio Rodriguez-Manfredi; Manuel de la Torre Juárez (Icarus, 2025)

Corn silk as an underutilized sustainable source of plant proteins: Extraction, fractionation, structure, and techno-functional properties - Jose C. Orellana-Palacios; Samuel Rodriguez Garcia; Yoana Rabanal-Ruiz; David Julian McClements; Andres Moreno; Milad Hadidi (Food Hydrocolloids, 2025)

Occurrence, characterization, and ecological risk analysis of petroleum hydrocarbons in water and sediments following large-scale field simulated oil spills at the experimental lakes area, Northwestern Ontario, Canada - Zeyu Yang; Keval Shah; Bruce Hollebone; Sonia Laforest; Madison MacGillivray; Diane Dey; Jose Luis Rodriguez; Benoit Lalonde; Chun Yang; Vanessa Beaulac; Jules M. Blais; Mark Hanson; et al. (Marine Pollution Bulletin, 2024)

Analysing long-term spatiotemporal land surface phenology patterns over the Iberian Peninsula using 250 m MODIS EVI2 data - Jose A. Caparros-Santiago; Victor Rodriguez-Galiano (Science of The Total Environment, 2024)

Simultaneous degradation of cyanobacteria and cyanotoxins by catalytic wet peroxide oxidation: Impact of morphology and growth stage - David Ortiz; Alicia Martin-Montero; Cristian Rodriguez; Neus Lopez-Arago; Samuel Cirés; Andreas Ballot; Zahara M. de Pedro; Antonio Quesada; Jose A. Casas; Macarena Munoz (Journal of Environmental Chemical Engineering, 2024)

Evaluation of ploidy and the DNA index by flow cytometry in central nervous system tumors: a review - Fernandez-Sanchez David; Ramirez-Corona Juan Antonio; Perez-Becerra Jose de Jesus; Santana-Bejarano Uriel Francisco; Santana-Hernandez Jennifer; Corona-Rivera Alfredo; Rodriguez-Machuca Victor Ulises; Bobadilla-Morales Lucina (Molecular Biology Reports, 2024)

Correction: Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria J. de Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

Long-term antigen-specific immune response by an oncolytic adenovirus encoding SP-SA-E7-4-1BBL in HPV-16 cancer model - Alejandra G. Martinez-Perez; Rodolfo Garza-Morales; Maria de J. Loera-Arias; Sheila A. Villa-Cedillo; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Orlando E. Flores-Maldonado; Jesus Valdes; Jose J. Perez-Trujillo; Odila Saucedo-Cardenas (Molecular Biology Reports, 2024)

Analysis of stallion spermatozoa metabolism using Agilent Seahorse XFp Technology - Jose Manuel Ortiz-Rodriguez; Diego Bucci; Laura Tovar-Pascual; Silvia Granata; Marcella Spinaci; Salvatore Nesci (Animal Reproduction Science, 2024)

Single-step preparation of activated carbons from pine wood, olive stones and nutshells by KOH and microwaves: Influence of ultra-microporous for high CO2 capture - Gabriela Duran-Jimenez; Jose Rodriguez; Lee Stevens; Sanad Altarawneh; Andrew Batchelor; Long Jiang; Chris Dodds (Chemical Engineering Journal, 2024)

Sustainable proteins from wine industrial by-product: Ultrasound-assisted extraction, fractionation, and characterization - Samuel Rodriguez Garcia; Jose C. Orellana-Palacios; David Julian McClements; Andres Moreno; Milad Hadidi (Food Chemistry, 2024)

Thermo-hydrochemical modelling of vertical profiles of the formed Meirama Lake (NW Spain) - Ricardo Juncosa; Jorge Delgado; Jose Cereijo; Pablo Rodriguez-vellando (Sustainable Water Resources Management, 2024)

A comparison of batch and semi-batch reactors for leaching battery cathodes (LiCoO2) under controlled addition of HCl and H2O2 - Maria del Mar Cerrillo-Gonzalez; Maria Villen-Guzman; Alvaro Rivas-Bascon; Jose Miguel Rodriguez-Maroto; Juan Manuel Paz-Garcia (Hydrometallurgy, 2024)

Effect of virgin olive oil as spreadable preparation on atherosclerosis compared to dairy butter in Apoe-deficient mice - Roberto Martínez-Beamonte; Cristina Barranquero; Sonia Gascón; Juan Mariño; Carmen Arnal; Gloria Estopañán; María Jesús Rodriguez-Yoldi; Joaquín Carlos Surra; Olga Martín-Belloso; Isabel Odriozola-Serrano; Israel Orman; Jose Carlos Segovia; et al. (Journal of Physiology and Biochemistry, 2024)
Olive oil is the main source of lipid energy in the Mediterranean diet and there is strong evidence of its health benefits. The effect of extra virgin olive oil (EVOO) in the form of a preparation of spreadable virgin olive oil (S-VO) on the progression of atheroma plaques was investigated in Apoe -deficient mice, a model of accelerated atherosclerosis. Methods: Two isocaloric Western purified diets containing 20% fat, either as S-VO or as dairy butter, were used to feed 28 males and 16 females of two-month-old Apoe -deficient mice for 12 weeks. S-VO was prepared by blending more than 75% virgin olive oil with other vegetal natural fat to obtain a solid fat. Plasma total cholesterol, triglycerides and HDL cholesterol were measured. Hepatic lipid droplets were analyzed. Areas of atherosclerotic aortic lesions were quantified in cross-sectional images of the proximal aorta and en face analysis of the whole aorta. Results: Total plasma cholesterol was increased in mice on the butter-supplemented diet in both female and male mice compared to S-VO, and the ratio of TC/HDL-cholesterol was significantly lower in S-VO than in the butter diet, although only in males, and no differences in plasma triglycerides were observed. No significant differences in hepatic lipid droplets were observed between diets in either sex. Aortic lesion areas were significantly higher in mice consuming the butter versus the S-VO diet in both sexes. Conclusion: Extra virgin olive oil prepared in spreadable form maintained the delay in atheroma plaque progression compared to butter.

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Chromatographic enantioresolution and stereochemical characterization of synthetic cannabinoid receptor agonists with Whelk-O®1 chiral stationary phases under mass spectrometry compatible reversed-phase conditions: A study case with seized samples - Ina Varfaj; Michele Protti; Alessandro Di Michele; Jose Gonzalez-Rodriguez; Andrea Carotti; Roccaldo Sardella; Laura Mercolini (Analytica Chimica Acta, 2024)

Impact of Tissue Damage and Hemodynamics on Restenosis Following Percutaneous Transluminal Angioplasty: A Patient-Specific Multiscale Model - Anna Corti; Matilde Marradi; Cemre Çelikbudak Orhon; Francesca Boccafoschi; Philippe Büchler; Jose F. Rodriguez Matas; Claudio Chiastra (Annals of Biomedical Engineering, 2024)
Multiscale agent-based modeling frameworks have recently emerged as promising mechanobiological models to capture the interplay between biomechanical forces, cellular behavior, and molecular pathways underlying restenosis following percutaneous transluminal angioplasty (PTA). However, their applications are mainly limited to idealized scenarios. Herein, a multiscale agent-based modeling framework for investigating restenosis following PTA in a patient-specific superficial femoral artery (SFA) is proposed. The framework replicates the 2-month arterial wall remodeling in response to the PTA-induced injury and altered hemodynamics, by combining three modules: (i) the PTA module, consisting in a finite element structural mechanics simulation of PTA, featuring anisotropic hyperelastic material models coupled with a damage formulation for fibrous soft tissue and the element deletion strategy, providing the arterial wall damage and post-intervention configuration, (ii) the hemodynamics module, quantifying the post-intervention hemodynamics through computational fluid dynamics simulations, and (iii) the tissue remodeling module, based on an agent-based model of cellular dynamics. Two scenarios were explored, considering balloon expansion diameters of 5.2 and 6.2 mm. The framework captured PTA-induced arterial tissue lacerations and the post-PTA arterial wall remodeling. This remodeling process involved rapid cellular migration to the PTA-damaged regions, exacerbated cell proliferation and extracellular matrix production, resulting in lumen area reduction up to 1-month follow-up. After this initial reduction, the growth stabilized, due to the resolution of the inflammatory state and changes in hemodynamics. The similarity of the obtained results to clinical observations in treated SFAs suggests the potential of the framework for capturing patient-specific mechanobiological events occurring after PTA intervention.

The imprint of coevolving semi-arid landscapes, soil, and vegetation on soil moisture and vegetation variability - Ankur Srivastava; Omer Yetemen; Jose F. Rodriguez; Nikul Kumari; Patricia M. Saco (CATENA, 2024)

Microdiversity in marine pelagic ammonia‐oxidizing archaeal populations in a Mediterranean long‐read metagenome - Pablo Suárez‐Moo; Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera (Environmental Microbiology, 2024)
The knowledge of the different population‐level processes operating within a species, and the genetic variability of the individual prokaryotic genomes, is key to understanding the adaptability of microbial populations. Here, we characterized the flexible genome of ammonia‐oxidizing archaeal (AOA) populations using a metagenomic recruitment approach and long‐read (PacBio HiFi) metagenomic sequencing. In the lower photic zone of the western Mediterranean Sea (75 m deep), the genomes Nitrosopelagicus brevis CN25 and Nitrosopumilus catalinensis SPOT1 had the highest recruitment values among available complete AOA genomes. They were used to analyse the diversity of flexible genes (variable from strain to strain) by examining the long‐reads located within the flexible genomic islands (fGIs) identified by their under‐recruitment. Both AOA genomes had a large fGI involved in the glycosylation of exposed structures, highly variable, and rich in glycosyltransferases. N. brevis had two fGIs related to the transport of phosphorus and ammonium respectively. N. catalinensis had fGIs involved in phosphorus transportation and metal uptake. A fGI5 previously reported as ‘unassigned function’ in N. brevis could be associated with defense. These findings demonstrate that the microdiversity of marine microbe populations, including AOA, can be effectively characterized using an approach that incorporates third‐generation sequencing metagenomics.

A Bayesian Multiplex Graph Classifier of Functional Brain Connectivity Across Diverse Tasks of Cognitive Control - Sharmistha Guha; Jose Rodriguez-Acosta; Ivo D. Dinov (Neuroinformatics, 2024)

Microwave pyrolysis of waste biomass and synthesis of micro-mesoporous activated carbons: The role of textural properties for CO2 and textile dye adsorption - Gabriela Durán-Jiménez; Jose Rodriguez; Lee Stevens; Emily T. Kostas; Chris Dodds (Chemical Engineering Journal, 2024)

Short-term associations between fine particulate air pollution and cardiovascular and respiratory mortality in 337 cities in Latin America - Nelson Gouveia; Jordan L. Rodriguez-Hernandez; Josiah L. Kephart; Ana Ortigoza; Ricardo Morales Betancourt; Jose Luis Texcalac Sangrador; Daniel A. Rodriguez; Ana V. Diez Roux; Brisa Sanchez; Goro Yamada (Science of The Total Environment, 2024)

Extracellular cAMP and MRP4 activity influence in vitro capacitation and fertilizing ability of pig spermatozoa - Marcella Spinaci; Olga Blanco-Prieto; Jose Manuel Ortiz-Rodriguez; Chiara Bernardini; Diego Bucci (Research in Veterinary Science, 2024)

Homogeneous vs. heterogeneous photo-Fenton elimination of antibiotic-resistant bacteria bearing intracellular or extracellular resistance: Do resistance mechanisms interfere with disinfection pathways? - Jeremie Decker; Truong-Thien Melvin Le; Jose Manuel Entenza; Isabel del Castillo Gonzalez; Aurelio Hernandez Lehmann; Cesar Pulgarin; Jorge Rodriguez-Chueca; Stefanos Giannakis (Journal of Environmental Chemical Engineering, 2024)

Controlled Elicitation and Greenhouse Acclimation Time Effects on Morphological and Biochemical Variables in Collections of Heliopsis longipes from Central México - Ixchel Parola-Contreras; Luis Felipe Guzman-Rodriguez; Erik Gustavo Tovar-Perez; Brenda Zulema Guerrero-Aguilar; Blanca Amalia Amaro-Gonzalez; Alejandra Rojas-Molina; Irineo Torres-Pacheco; Jose Luis Pons-Hernandez; Mario Martin Gonzalez-Chavira; Ramon Gerardo Guevara-Gonzalez (Journal of Plant Growth Regulation, 2024)

Human health and environmental risk assessment of metals in community gardens of Winnipeg, Manitoba, Canada - Teresa Senderewich; Doug Goltz; Jose Luis Rodriguez-Gil; Brian Laird; Ryan S. Prosser; Mark L. Hanson (Environmental Science and Pollution Research, 2024)

Multi-omic characterization of mechanisms contributing to rapid phenotypic plasticity in the coral Acropora cervicornis under divergent environments - Javier A. Rodriguez-Casariego; Alex Mercado-Molina; Leila Soledade Lemos; Natalia Soares Quinete; Anthony Bellantuono; Mauricio Rodriguez-Lanetty; Alberto Sabat; Jose M. Eirin-Lopez (Coral Reefs, 2024)

Crustal structure of the Western Azuero Peninsula, Panama: Insights into the structure of accretionary complexes and forearc ophiolites - Carolina Ortiz-Guerrero; Camilo Montes; David W. Farris; Catalina Agudelo; Margarita Ariza Acero; Juliana Ayala; Jose David Avellaneda; Alejandro Cortes-Calderon; Esteban Gaitan; Sebastian Garzon; Daniel Gongora-Blanco; Nubia Andrea Jara; et al. (International Geology Review, 2024)

Bottom fishing beyond trawling. Spatio-temporal trends of mobile and static bottom fisheries on benthic habitats - Ulla Fernandez-Arcaya; Augusto Rodríguez-Basalo; Patricia Verísimo; José Rodriguez; Elvira Ceballos; Jose Manuel Gonzalez-Irusta; Ana García-Alegre; Maider Plaza-Morlote; Alberto Serrano; Antonio Punzón (Marine Policy, 2024)

Monitoring long-term vegetation condition dynamics in persistent semi-arid wetland communities using time series of Landsat data - Li Wen; Tanya J. Mason; Shawn Ryan; Joanne E. Ling; Neil Saintilan; Jose Rodriguez (Science of The Total Environment, 2023)

Modulation of the lipolysis and subsequent antibacterial activity of the fat from black soldier fly (Hermetia illucens) by the combined selection of slaughtering, drying and defatting methods of the larvae - Raúl Hurtado-Ribeira; Jose Manuel Silvan; Tiziana Fornari; Luis Vázquez; Adolfo J. Martinez-Rodriguez; Diana Martin (Innovative Food Science & Emerging Technologies, 2023)

Considerations on the action of polyphenoloxidase on 4-hydroxy-cinnamic acid. Molecular docking simulation - Pablo García Molina; Jose Antonio Teruel Puche; Jose Luis Muñoz Muñoz; Jose Neptuno Rodriguez Lopez; Francisco García Canovas; Francisco García Molina (Food Chemistry, 2023)

Design recommendations for the rehabilitation of an urban canyon in a subtropical climate region using aerial thermography and simulation tools - Marta Videras Rodriguez; Sergio Gomez Melgar; Jose Manuel Andujar Marquez (Energy and Buildings, 2023)

Matrix changes driven by cultivar diversity, inulin addition and drying techniques - shaping the antioxidant, antimicrobial and anti-inflammatory properties of blueberry powders - Jessica Brzezowska; Adolfo J. Martinez-Rodriguez; Jose Manuel Silvan; Grzegorz P. Łysiak; Aneta Wojdyło; Krzysztof Lech; Anna Michalska-Ciechanowska (Innovative Food Science & Emerging Technologies, 2023)

Smoking, blood DNA methylation sites and lung cancer risk - Arce Domingo-Relloso; Roby Joehanes; Zulema Rodriguez-Hernandez; Lies Lahousse; Karin Haack; M. Daniele Fallin; Miguel Herreros-Martinez; Jason G. Umans; Lyle G. Best; Tianxiao Huan; Chunyu Liu; Jiantao Ma; et al. (Environmental Pollution, 2023)

Adsorbents obtained from recycled polymeric materials for retention of different pollutants: A review - Karen A. Escamilla-Lara; Jorge Lopez-Tellez; Jose A. Rodriguez (Chemosphere, 2023)

Effect of the historic Spanish heatwave over glycemic control in adult patients with type 1 diabetes - Jesus Moreno-Fernandez; Julia Sastre; Sandra Herranz; Pedro Pinés; Francisco Javier Gomez; Ivan Quiroga; Antonio Jose Moya; Cesar Gonzalvo; Raquel Miralles; Dulce Calderon-Vicente; Mercedes Palma; Javier Gargallo; et al. (Science of The Total Environment, 2023)

Ambient temperature modulates body weight changes in patients with advanced oncological diseases and anorexia cachexia syndrome - Paloma Encinas; Jose Luis Rodriguez-Arias; Luis Miguel Luengo Pérez; Daniel Cortizo; Emilio Gutierrez (International Journal of Biometeorology, 2023)
Objective To assess the impact of ambient temperature (AT) on the evolution of bodyweight in patients with heterogeneous types of cancer in advanced stages of the disease (stages III and IV) and anorexia- cachexia syndrome (ACS). Methods A prospective naturalistic multicenter study of patients undergoing oncological treatment at four hospitals during a three-year period (2017–2020) in the Autonomous Community of Extremadura in southwestern Spain with a continentalized Mediterranean climate of mild and relatively rainy winters, and particularly hot and sunny summers. Bodyweight changes were obtained from the medical records of 84 oncological patients (59 men and 25 women, age range 37–91 yrs). Mean monthly AT was used to examine the association of weight changes across cold and warm bimesters -BIMs (December and January, vs. July and August), Trimesters -TRIMs (July to September vs. December to February), and Semesters -SEMs (May to October vs. November to April). Weight changes between two consecutive weight measures were categorized as weight gain, weight loss, or no weight change. Differences across cold and warm seasons were analysed using parametric (ANOVA), and nonparametric statistics (Chi-square and binomial z tests). An alpha-rate of 0.05 was used for all analyses. Results A weight loss trend was observed during BIMs cold periods in comparison to warm ones ( p 0.04). However, differences in average bodyweight were not significant. The negative impact of cold periods was more marked in men than in women, ( p = 0.05; p = 0.03, for cold vs. warm BIMs and TRIMs, respectively). In contrast, significantly higher weight gain percentages were found in women during warm TRIMs and SEMs ( p = 0.03, and p = 0.01, respectively). As for the number of patients dying during the study ( N = 56; 39 men, 17 women), there were a significant interaction between temperature (cold/warm), and mean weight F ( 1, 499) = 6.06, p = 0.01, which revealed a pattern of weight loss in the cold semester as opposed to weight gain during the warm SEM months. Conclusions AT temperature modulated body weight changes in patients with advanced oncological disease and ACS. Two main limitations of the study were the absence of information on diets as a moderating factor of weight loss/gain, and the lack of the patients’ weight measurements closest to the date of diagnosis prior to admittance to the study. As for the practical implications, it remains to be seen whether an adjunctive heat supply will serve a buffering effect on weight loss during colder seasons for patients with advanced cancer and ACS.

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

Life history and stock synthesis assessment of Prionotus punctatus (Teleostei, Triglidae) in southern Brazil - Andrea Renata Rodriguez; Manuel Haimovici; Eidi Kikuchi; Rodrigo Sant'Ana; Bruno L. Mourato; Jose Angel Alvarez Perez; Luís Gustavo Cardoso (Fisheries Management and Ecology, 2023)
Age, growth, and maturity of the bluewing searobin Prionotus punctatus were studied to assess its stock status in southern Brazil. Total length compositions, weight, sex, and maturity stage were recorded from commercial landings, and ages were estimated from transverse sections of the sagittal otolith. The oldest observed specimen was a 12‐year‐old female. Females grew to a larger asymptotic length ( L ∞ = 384.4 mm) than males ( L ∞ = 311.7 mm) but at a slower instantaneous rate ( k females = 0.41 year −1 , k males = 0.75 year −1 ). Reproduction occurred from spring to early fall. Females size‐ and age‐at‐maturity was estimated at 246.8 mm and 1.66 years, while males were at 237.2 mm and 1.38 years. Based on a statistical catch‐at‐age stock assessment, the spawning biomass declined 84% from 1976 to 2000 being classified as overfished and suffering from overfishing (B/B msy = 0.62; F/ Fmsy >1). P. punctatus was regularly discarded by industrial fisheries before 2000 but suffered from high exploitation in the last decades. These results highlight the need for the species to be included in Brazil's fishery management plans.

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Kinetic study of the catalytic cracking of waste motor oil using biomass-derived heterogeneous catalysts - Yuliana Rodriguez; Renato Guerra; Karla Vizuete; Alexis Debut; Daniela Almeida Streitwieser; Jose R. Mora; Sebastian Ponce (Waste Management, 2023)

Influence of secretome obtained from preovulatory follicular fluid on energy metabolism and meiotic competence of equine cumulus–oocyte complexes - Jose M Ortiz-Rodriguez; Pablo Fernández-Hernández; Marcos Luis-Calero; Marcella Spinaci; Diego Bucci; Beatriz Macías-García; Lauro González-Fernández (Journal of Equine Veterinary Science, 2023)

Effect of transvaginal oocyte aspiration on progesterone concentrations and estrous cycle length in domestic jennies - Ana Flores Bragulat; Carolina Alonso; Catalina Castañeira; Ayelen Rodriguez; Jose M Zeledon; Luis Losinno; Andres Gambini (Journal of Equine Veterinary Science, 2023)

Efficiency of equine oocyte recovery from post mortem ovaries or by ovum pick up - Catalina Castañeira; Ana P Flores Bragulat; Carolina N Alonso; Ayelen M Rodriguez; Guido A Rocchi; Jose M Zeledon (Journal of Equine Veterinary Science, 2023)

Single‐amplified genomes reveal most streamlined free‐living marine bacteria - Juan J. Roda‐Garcia; Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Salvador Almagro‐Moreno; Mario López‐Pérez (Environmental Microbiology, 2023)
Evolutionary adaptations of prokaryotes to the environment sometimes result in genome reduction. Our knowledge of this phenomenon among free‐living bacteria remains scarce. We address the dynamics and limits of genome reduction by examining one of the most abundant bacteria in the ocean, the SAR86 clade. Despite its abundance, comparative genomics has been limited by the absence of pure cultures and the poor representation in metagenome‐assembled genomes. We co‐assembled multiple previously available single‐amplified genomes to obtain the first complete genomes from members of the four families. All families showed a convergent evolutionary trajectory with characteristic features of streamlined genomes, most pronounced in the TMED112 family. This family has a genome size of ca. 1 Mb and only 1 bp as median intergenic distance, exceeding values found in other abundant microbes such as SAR11, OM43 and Prochlorococcus . This genomic simplification led to a reduction in the biosynthesis of essential molecules, DNA repair‐related genes, and the ability to sense and respond to environmental factors, which could suggest an evolutionary dependence on other co‐occurring microbes for survival (Black Queen hypothesis). Therefore, these reconstructed genomes within the SAR86 clade provide new insights into the limits of genome reduction in free‐living marine bacteria.

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Preparation, characterization, and antioxidant activity of β-cyclodextrin nanoparticles loaded Rosa damascena essential oil for application in beverage - Zahra Hadian; Mahdie Kamalabadi; Yuthana Phimolsiripol; Balamuralikrishnan Balasubramanian; Jose Manuel Lorenzo Rodriguez; Amin Mousavi Khaneghah (Food Chemistry, 2023)

Corrigendum to “Forest Hydrology in Chile; paste, present, and future” [J. Hydrol. 616 (2023)] - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barria; et al. (Journal of Hydrology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Consumption of Foods Away from Home Is Associated with Lower Diet Quality Among Adults Living in Puerto Rico - Nayla Bezares; Amanda C. McClain; Martha Tamez; Jose F. Rodriguez-Orengo; Katherine L. Tucker; Josiemer Mattei (Journal of the Academy of Nutrition and Dietetics, 2023)

Forest hydrology in Chile: Past, present, and future - Francisco Balocchi; Mauricio Galleguillos; Diego Rivera; Alejandra Stehr; Jose Luis Arumi; Roberto Pizarro; Pablo Garcia-Chevesich; Andrés Iroumé; Juan J. Armesto; Pedro Hervé-Fernández; Carlos Oyarzún; Pilar Barría; et al. (Journal of Hydrology, 2023)

Evaluation of inhibitory effects of some novel phenolic derivatives on the mushroom tyrosinase activity - Pablo García Molina; Jose Luis Muñoz Muñoz; Jose Antonio Teruel Puche; Jose Neptuno Rodriguez Lopez; Francisco Garcia Canovas; Francisco Garcia Molina (Food Chemistry, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Validation and Verification of High-Fidelity Simulations of Thoracic Stent-Graft Implantation - Anna Ramella; Francesco Migliavacca; Jose Felix Rodriguez Matas; Frederic Heim; Francesca Dedola; Stefania Marconi; Michele Conti; Sara Allievi; Tim J. Mandigers; Daniele Bissacco; Maurizio Domanin; Santi Trimarchi; et al. (Annals of Biomedical Engineering, 2022)
Thoracic Endovascular Aortic Repair (TEVAR) is the preferred treatment option for thoracic aortic pathologies and consists of inserting a self-expandable stent-graft into the pathological region to restore the lumen. Computational models play a significant role in procedural planning and must be reliable. For this reason, in this work, high-fidelity Finite Element (FE) simulations are developed to model thoracic stent-grafts. Experimental crimp/release tests are performed to calibrate stent-grafts material parameters. Stent pre-stress is included in the stent-graft model. A new methodology for replicating device insertion and deployment with explicit FE simulations is proposed. To validate this simulation, the stent-graft is experimentally released into a 3D rigid aortic phantom with physiological anatomy and inspected in a computed tomography (CT) scan at different time points during deployment with an ad-hoc set-up. A verification analysis of the adopted modeling features compared to the literature is performed. With the proposed methodology the error with respect to the CT is on average 0.92 ± 0.64%, while it is higher when literature models are adopted (on average 4.77 ± 1.83%). The presented FE tool is versatile and customizable for different commercial devices and applicable to patient-specific analyses.

Cellular heterogeneity and repolarisation across the atria: an in silico study - Jordan Elliott; Luca Mainardi; Jose Felix Rodriguez Matas (Medical & Biological Engineering & Computing, 2022)
Mechanisms of atrial fibrillation and the susceptibility to reentries can be impacted by the repolarization across the atria. Studies into atrial fibrillation ignore cell-to-cell heterogeneity due to electrotonic coupling. Recent studies show that cellular variability may have a larger impact on electrophysiological behaviour than assumed. This paper aims to determine the impact of cellular heterogeneity on the repolarization phase across the AF remodelled atria. Using a population of models approach, 10 anatomically identical atrial models were created to include cellular heterogeneity. Atrial models were compared with an equivalent homogenous model. Activation, APD90, and repolarization maps were used to compare models. The impact of electrotonic coupling in the tissue was determined through a comparison of RMP, APD20, APD50, APD90, and triangulation between regional atrial tissue and the single cell populations. After calibration, cellular heterogeneity does not impact atrial depolarization. Repolarization patterns were significantly impacted by cellular heterogeneity, with the APD90 across the LA increasing due to heterogeneity and the reverse occurring in the RA. Electrotonic coupling caused a reduction in variability across all biomarkers but did not fully remove variability. Electrotonic coupling resulted in an increase in APD20 and APD50, and reduced triangulation compared to isolated cell populations. Heterogeneity also caused a reduction in triangulation compared with regionally homogeneous atria. Graphical abstract

Soil macroinvertebrate communities: A world‐wide assessment - Patrick Lavelle; Jérôme Mathieu; Alister Spain; George Brown; Carlos Fragoso; Emmanuel Lapied; Adriana De Aquino; Isabelle Barois; Edmundo Barrios; Maria Eleusa Barros; Jose Camilo Bedano; Eric Blanchart; et al. (Global Ecology and Biogeography, 2022)
Aim Macroinvertebrates comprise a highly diverse set of taxa with great potential as indicators of soil quality. Communities were sampled at 3,694 sites distributed world‐wide. We aimed to analyse the patterns of abundance, composition and network characteristics and their relationships to latitude, mean annual temperature and rainfall, land cover, soil texture and agricultural practices. Location Sites are distributed in 41 countries, ranging from 55° S to 57° N latitude, from 0 to 4,000 m in elevation, with annual rainfall ranging from 500 to >3,000 mm and mean temperatures of 5–32°C. Time period 1980–2018. Major taxa studied All soil macroinvertebrates: Haplotaxida; Coleoptera; Formicidae; Arachnida; Chilopoda; Diplopoda; Diptera; Isoptera; Isopoda; Homoptera; Hemiptera; Gastropoda; Blattaria; Orthoptera; Lepidoptera; Dermaptera; and “others”. Methods Standard ISO 23611‐5 sampling protocol was applied at all sites. Data treatment used a set of multivariate analyses, principal components analysis (PCA) on macrofauna data transformed by Hellinger’s method, multiple correspondence analysis for environmental data (latitude, elevation, temperature and average annual rainfall, type of vegetation cover) transformed into discrete classes, coinertia analysis to compare these two data sets, and bias‐corrected and accelerated bootstrap tests to evaluate the part of the variance of the macrofauna data attributable to each of the environmental factors. Network analysis was performed. Each pairwise association of taxonomic units was tested against a null model considering local and regional scales, in order to avoid spurious correlations. Results Communities were separated into five clusters reflecting their densities and taxonomic richness. They were significantly influenced by climatic conditions, soil texture and vegetation cover. Abundance and diversity, highest in tropical forests (1,895 ± 234 individuals/m 2 ) and savannahs (1,796 ± 72 individuals/m 2 ), progressively decreased in tropical cropping systems (tree‐associated crops, 1,358 ± 120 individuals/m 2 ; pastures, 1,178 ± 154 individuals/m 2 ; and annual crops, 867 ± 62 individuals/m 2 ), temperate grasslands (529 ± 60 individuals/m 2 ), forests (232 ± 20 individuals/m 2 ) and annual crops (231 ± 24 individuals/m 2 ) and temperate dry forests and shrubs (195 ± 11 individuals/m 2 ). Agricultural management decreased overall abundance by ≤54% in tropical areas and 64% in temperate areas. Connectivity varied with taxa, with dominant positive connections in litter transformers and negative connections with ecosystem engineers and Arachnida. Connectivity and modularity were higher in communities with low abundance and taxonomic richness. Main conclusions Soil macroinvertebrate communities respond to climatic, soil and land‐cover conditions. All taxa, except termites, are found everywhere, and communities from the five clusters cover a wide range of geographical and environmental conditions. Agricultural practices significantly decrease abundance, although the presence of tree components alleviates this effect.

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Health risk assessment associated to heavy metal pollution levels in Mediterranean environment soils: a case study in the watershed of Sebkhet Ariana, Tunisia - Amal Ghouma; Abdelwaheb Aydi; Jose Antonio Rodriguez Martin; Mohamed Gasmi (Arabian Journal of Geosciences, 2022)

Symbiont shuffling induces differential DNA methylation responses to thermal stress in the coral Montastraea cavernosa - Javier A. Rodriguez‐Casariego; Ross Cunning; Andrew C. Baker; Jose M. Eirin‐Lopez (Molecular Ecology, 2022)
Algal symbiont shuffling in favour of more thermotolerant species has been shown to enhance coral resistance to heat‐stress. Yet, the mechanistic underpinnings and long‐term implications of these changes are poorly understood. This work studied the modifications in coral DNA methylation, an epigenetic mechanism involved in coral acclimatization, in response to symbiont manipulation and subsequent heat stress exposure. Symbiont composition was manipulated in the great star coral Montastraea cavernosa through controlled thermal bleaching and recovery, producing paired ramets of three genets dominated by either their native symbionts (genus Cladocopium ) or the thermotolerant species ( Durusdinium trenchi ). Single‐base genome‐wide analyses showed significant modifications in DNA methylation concentrated in intergenic regions, introns and transposable elements. Remarkably, DNA methylation changes in response to heat stress were dependent on the dominant symbiont, with twice as many differentially methylated regions found in heat‐stressed corals hosting different symbionts ( Cladocopium vs. D . trenchii ) compared to all other comparisons. Interestingly, while differential gene body methylation was not correlated with gene expression, an enrichment in differentially methylated regions was evident in repetitive genome regions. Overall, these results suggest that changes in algal symbionts favouring heat tolerant associations are accompanied by changes in DNA methylation in the coral host. The implications of these results for coral adaptation, along with future avenues of research based on current knowledge gaps, are discussed in the present work.

Interplay between IncF plasmids and topoisomerase mutations conferring quinolone resistance in the Escherichia coli ST131 clone: stability and resistance evolution - Jose-Manuel Rodríguez-Martínez; Lorena Lopez-Cerero; Ana García-Duque; Jesus Rodriguez-Baño; Alvaro Pascual (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
The Escherichia coli ST131 H30 -Rx subclone vehicles CTX-M-15 plasmids and mutations in gyrA and parC conferring multidrug resistance successfully in the clinical setting. The aim of this study was (1) to investigate the relationship of specific topoisomerase mutations on the stability of IncF (CTX-M producing) plasmids using isogenic E. coli mutants and (2) to investigate the impact of the IncF-type plasmids present in the E. coli clone ST131 on the evolution of quinolone resistance. E. coli ATCC 25922 (background strain) and derived mutants encoding specific QRDR substitutions were used. Also, NGS-characterized IncFIA and IncFIB plasmids (encoding CTX-M genes) were included. Plasmid stability was evaluated by sequential dilutions into Luria broth medium without antibiotics for 7 days. Mutant frequency to ciprofloxacin was also evaluated. Moderate differences in the IncF plasmids stability were observed among E. coli ATCC 25922 and isogenic mutants. Under our experimental conditions, the fluctuation of bacteria harboring plasmids was less than 0.5-log (10) in all cases. In the mutant frequency tests, it was observed that the presence of these IncF plasmids increased this value significantly (10–1000-fold). Quinolone resistance substitutions in gyrA or parC genes, frequently found associated with E. coli clone ST131, do not modify the stability of ST131-associated IncFIA and IncFIB plasmids under in vitro conditions. IncF-type plasmids present in E. coli clone ST131 facilitate the selection of resistance to quinolones. These results are consistent with the clinical scenario in which the combination of resistance to quinolones and beta-lactams is highly frequent in the E. coli clone ST131.

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Combining 4D Flow MRI and Complex Networks Theory to Characterize the Hemodynamic Heterogeneity in Dilated and Non-dilated Human Ascending Aortas - Karol Calò; Diego Gallo; Andrea Guala; Jose Rodriguez Palomares; Stefania Scarsoglio; Luca Ridolfi; Umberto Morbiducci (Annals of Biomedical Engineering, 2021)
Motivated by the evidence that the onset and progression of the aneurysm of the ascending aorta (AAo) is intertwined with an adverse hemodynamic environment, the present study characterized in vivo the hemodynamic spatiotemporal complexity and organization in human aortas, with and without dilated AAo, exploring the relations with clinically relevant hemodynamic and geometric parameters. The Complex Networks (CNs) theory was applied for the first time to 4D flow magnetic resonance imaging (MRI) velocity data of ten patients, five of them presenting with AAo dilation. The time-histories along the cardiac cycle of velocity-based quantities were used to build correlation-based CNs. The CNs approach succeeded in capturing large-scale coherent flow features, delimiting flow separation and recirculation regions. CNs metrics highlighted that an increasing AAo dilation (expressed in terms of the ratio between the maximum AAo and aortic root diameter) disrupts the correlation in forward flow reducing the correlation persistence length, while preserving the spatiotemporal homogeneity of secondary flows. The application of CNs to in vivo 4D MRI data holds promise for a mechanistic understanding of the spatiotemporal complexity and organization of aortic flows, opening possibilities for the integration of in vivo quantitative hemodynamic information into risk stratification and classification criteria.

Evidence of A tlantic bluefin tuna spawning in the B ay of B iscay, north‐eastern A tlantic - Jose M. Rodriguez; Carolina Johnstone; Diego Lozano‐Peral (Journal of Fish Biology, 2021)
The spawning grounds of the Atlantic bluefin tuna ( Thunnus thynnus ) are traditionally considered to be the Gulf of Mexico (Gulf of Mexico) and the Mediterranean Sea (Mediterranean Sea). However, for the western Atlantic, unequivocal evidence of bluefin spawning outside the Gulf of Mexico has been shown. In this study we present the first records of genetically confirmed bluefin larvae in the southern Bay of Biscay (eastern Atlantic). These findings provide evidence of bluefin spawning activity outside the Mediterranean Sea, in the north‐eastern Atlantic. However, our results suggest that the bluefin spawning in the Bay of Biscay is a sporadic phenomenon.

Successful Isavuconazole Salvage Therapy for a Cryptococcus deuterogattii (AFLP6/VGII) Disseminated Infection in a European Immunocompetent Patient - Maria Soledad Cuetara; Juan José Jusdado Ruiz-Capillas; Maria Pilar Nuñez-Valentin; Elena Rodríguez Garcia; Elena Garcia-Benayas; Ricardo Rojo-Amigo; Jose Carlos Rodriguez-Gallego; Ferry Hagen; María Francisca Colom (Mycopathologia, 2021)

Incidence, clinical characteristics, risk factors and outcomes of meningoencephalitis in patients with COVID-19 - Marcos Fragiel; Òscar Miró; Pere Llorens; Sònia Jiménez; Pascual Piñera Salmerón; Guillermo Burillo-Putze; Alfonso Martín; Francisco Javier Martín-Sánchez; Eric Jorge García Lamberechts; Javier Jacob; Aitor Alquézar-Arbé; Ferran Llopis-Roca; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

First evidence of fish nocardiosis in Mexico caused by Nocardia seriolae in farmed red drum ( Sciaenops ocellatus , Linnaeus) - Rodolfo Enrique del Rio‐Rodriguez; Jose Gustavo Ramirez‐Paredes; Sonia Araceli Soto‐Rodriguez; Yechiam Shapira; Mariana del Jesus Huchin‐Cortes; Judith Ruiz‐Hernandez; Monica Isela Gomez‐Solano; David J. Haydon (Journal of Fish Diseases, 2021)
Between August and December 2013, the offshore cages of a commercial marine farm culturing red drum Sciaenops ocellatus in Campeche Bay Mexico were affected by an outbreak of an ulcerative granulomatous disease with up to 70% cumulative mortality. Thirty‐one adults displaying open ulcers on the skin were submitted for diagnosis. At necropsy, multiple white‐yellowish nodules (0.1–0.5 cm in diameter) were present in all internal organs, where the kidney and the spleen were the most severely affected. Histopathology evinced typical systemic granulomatous formations. Gram and Ziehl–Neelsen stains on tissue imprints, bacterial swabs and tissue sections revealed Gram‐positive, acid‐fast, branching beaded long rod filamentous bacteria. Tissue samples resulted positive for nocardiosis with a Nocardia genus‐specific nested PCR. Definite identification at the species level and taxonomic positioning of the fastidious pathogen were achieved through a specific Nocardia seriolae PCR and by sequencing the gyrB gene of pure isolates. After administration of antibiotics during fry production, a posterior follow‐up monitoring (from 2014 to 2017) detected mild but recurrent outbreaks of the bacteria with no seasonality pattern. To the extent of our knowledge, this is the first report of piscine nocardiosis in Mexico and the first time this disease is detected in red drum.

Biological production of H 2 , CH 4 and CO 2 in the deep subsurface of the Iberian Pyrite Belt - Jose L. Sanz; Nuria Rodriguez; Cristina Escudero; Daniel Carrizo; Ricardo Amils (Environmental Microbiology, 2021)
Summary Most of the terrestrial deep subsurfaces are oligotrophic environments in which some gases, mainly H 2 , CH 4 and CO 2 , play an important role as energy and/or carbon sources. In this work, we assessed their biotic and abiotic origin in samples from subsurface hard‐rock cores of the Iberian Pyrite Belt (IPB) at three different depths (414, 497 and 520 m). One set of samples was sterilized (abiotic control) and all samples were incubated under anaerobic conditions. Our results showed that H 2 , CH 4 and CO 2 remained low and constant in the sterilized controls while their levels were 4, 4.1 and 2.5 times higher respectively, in the unsterilized samples compared to the abiotic controls. The δ 13 C CH4 ‐values measured in the samples (range −31.2 to −43.0 ‰) reveals carbon isotopic signatures that are within the range for biological methane production. Possible microorganisms responsible for the biotic production of the gases were assessed by CARD‐FISH. The analysis of sequenced genomes of detected microorganisms within the subsurface of the IPB allowed to identify possible metabolic activities involved in H 2 ( Rhodoplanes , Shewanella and Desulfosporosinus ), CH 4 (Methanobacteriales) and CO 2 production. The obtained results suggest that part of the H 2 , CH 4 and CO 2 detected in the deep subsurface has a biological origin.

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

A Fuzzy Optimization Model for the Berth Allocation Problem and Quay Crane Allocation Problem (BAP + QCAP) with n Quays - Edwar Lujan; Edmundo Vergara; Jose Rodriguez-Melquiades; Miguel Jiménez-Carrión; Carlos Sabino-Escobar; Flabio Gutierrez (Journal of Marine Science and Engineering, 2021)
This work introduces a fuzzy optimization model, which solves in an integrated way the berth allocation problem (BAP) and the quay crane allocation problem (QCAP). The problem is solved for multiple quays, considering vessels’ imprecise arrival times. The model optimizes the use of the quays. The BAP + QCAP, is a NP-hard (Non-deterministic polynomial-time hardness) combinatorial optimization problem, where the decision to assign available quays for each vessel adds more complexity. The imprecise vessel arrival times and the decision variables—berth and departure times—are represented by triangular fuzzy numbers. The model obtains a robust berthing plan that supports early and late arrivals and also assigns cranes to each berth vessel. The model was implemented in the CPLEX solver (IBM ILOG CPLEX Optimization Studio); obtaining in a short time an optimal solution for very small instances. For medium instances, an undefined behavior was found, where a solution (optimal or not) may be found. For large instances, no solutions were found during the assigned processing time (60 min). Although the model was applied for n = 2 quays, it can be adapted to “n” quays. For medium and large instances, the model must be solved with metaheuristics.

A 3D construct based on mesenchymal stromal cells, collagen microspheres and plasma clot supports the survival, proliferation and differentiation of hematopoietic cells in vivo - Carlos Bello-Rodriguez; Olga Wittig; Dylana Diaz-Solano; Pura Bolaños; Jose E. Cardier (Cell and Tissue Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

A consumption-oriented approach to measuring regional food self-sufficiency - Dirk Godenau; Jose Juan Caceres-Hernandez; Gloria Martin-Rodriguez; Jose Ignacio Gonzalez-Gomez (Food Security, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ecogenomics of the SAR11 clade - Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Riccardo Rosselli; Francisco Martinez‐Hernandez; Juan J. Roda‐Garcia; Monica Lluesma Gomez; Oscar Fornas; Manuel Martinez‐Garcia; Mario López‐Pérez (Environmental Microbiology, 2020)
Summary Members of the SAR11 clade, despite their high abundance, are often poorly represented by metagenome‐assembled genomes. This fact has hampered our knowledge about their ecology and genetic diversity. Here we examined 175 SAR11 genomes, including 47 new single‐amplified genomes. The presence of the first genomes associated with subclade IV suggests that, in the same way as subclade V, they might be outside the proposed Pelagibacterales order. An expanded phylogenomic classification together with patterns of metagenomic recruitment at a global scale have allowed us to define new ecogenomic units of classification (genomospecies), appearing at different, and sometimes restricted, metagenomic data sets. We detected greater microdiversity across the water column at a single location than in samples collected from similar depth across the global ocean, suggesting little influence of biogeography. In addition, pangenome analysis revealed that the flexible genome was essential to shape genomospecies distribution. In one genomospecies preferentially found within the Mediterranean, a set of genes involved in phosphonate utilization was detected. While another, with a more cosmopolitan distribution, was unique in having an aerobic purine degradation pathway. Together, these results provide a glimpse of the enormous genomic diversity within this clade at a finer resolution than the currently defined clades.

Cryptococcal meningoencephalitis presenting as cerebral venous thrombosis - Jon Equiza; Gorka Fernandez-Eulate; Jon Rodriguez-Antigüedad; David Campo-Caballero; Amaia Muñoz-Lopetegi; Miguel-Angel Goenaga Sanchez; Jose Angel Larrea; Ana de Arce Borda (Journal of NeuroVirology, 2020)

Blood Flow-Restricted Training in Older Adults: A Narrative Review - Abel Plaza-Florido; Jairo H. Migueles; Antonio Piepoli; Pablo Molina-Garcia; Maria Rodriguez-Ayllon; Cristina Cadenas-Sanchez; Jose Mora-Gonzalez; Irene Esteban-Cornejo; Francisco B. Ortega (Journal of Science in Sport and Exercise, 2020)

Evaluation of occult hepatitis B infection in tissue donors: a multicenter analysis in Spain - Jacinto Sánchez Ibáñez; Ana Vilarrodona Serrat; Teresa Seoane Pillado; Clara Rodriguez Aierbe; Rafael Villalba Montoro; Javier Calvo Benito; Marta Pevida Lopez; Sergio Fernández Paneque; Elena Vuelta Lopez; Maria Jose Martínez Lorenzo; Manuel González Romero; Angelina Cañizares Castellanos; et al. (Cell and Tissue Banking, 2019)

On the Modeling of Patient-Specific Transcatheter Aortic Valve Replacement: A Fluid–Structure Interaction Approach - Giulia Luraghi; Francesco Migliavacca; Alberto García-González; Claudio Chiastra; Alexia Rossi; Davide Cao; Giulio Stefanini; Jose Felix Rodriguez Matas (Cardiovascular Engineering and Technology, 2019)

Novel Caudovirales associated with Marine Group I Thaumarchaeota assembled from metagenomes - Mario López‐Pérez; Jose M. Haro‐Moreno; José R. de la Torre; Francisco Rodriguez‐Valera (Environmental Microbiology, 2019)
Summary Marine Group I (MGI) Thaumarchaeota are some of the most abundant microorganisms in the deep ocean and responsible for much of the ammonia oxidation occurring in this environment. In this work, we present 35 sequences assembled from metagenomic samples of the first uncultivated Caudovirales viruses associated with Thaumarchaeota, which we designated marthavirus. Most of the sequences were obtained from cellular metagenomes confirming that they represent an important tool to study environmental viral communities due to cells retrieved while undergoing viral lysis. Metagenomic recruitment showed that this viral population is formed by very divergent entities with high intrapopulation homogeneity. However, metatranscriptomic analyses revealed the same differential expression profile with the capsid as major transcript, indicative of viruses during the lytic cycle. The cobalamine biosynthesis gene cob S, an auxiliary metabolic gene, was also highly expressed during the infection. These analyses expand our understanding of the global diversity of archaeal viruses.

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Immobilization of Brown Seaweeds Sargassum vulgare for Fe3+ Removal in Batch and Fixed-Bed Column - Souad Benaisa; Brahim Arhoun; Maria Villen-Guzman; Rachad El Mail; Jose Miguel Rodriguez-Maroto (Water, Air, & Soil Pollution, 2019)

Influence of salinity cycles in bioreactor performance and microbial community structure of membrane-based tidal-like variable salinity wastewater treatment systems - Alejandro Rodriguez-Sanchez; Juan Carlos Leyva-Diaz; Barbara Muñoz-Palazon; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2019)

Trophic ecology of European hake (Merlucius merlucius) larvae by stable isotopes analysis influenced by seasonal variability of oceanographic conditions off NW Galician waters. - Raul Carrion; Agueda Rodriguez; Jos M. Ervas; Alma De Rojas; Jose Maria Lopez; Piñeiro Carmen; Alberto Garcia (Frontiers in Marine Science, 2019)

Seasonal growth variability of young of the year European hake (Merluccius merluccius) off NW Spanish waters - Piñeiro Carmen; Lorena Fernandez; Jose Hervas; Agueda Rodriguez; Alberto Garcia (Frontiers in Marine Science, 2019)

Maximum Influent Salinity Affects the Diversity of Mineral-Precipitation-Mediating Bacterial Communities in Membrane Biofilm of Hybrid Moving Bed Biofilm Reactor-Membrane Bioreactor - Alejandro Rodriguez-Sanchez; Barbara Muñoz-Palazon; Miguel Hurtado-Martinez; Maria Angustias Rivadeneyra; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Water, Air, & Soil Pollution, 2018)

PTRF acts as an adipokine contributing to adipocyte dysfunctionality and ectopic lipid deposition - Sergio Perez-Diaz; Maria P. Garcia-Sobreviela; Yolanda Gonzalez-Irazabal; Beatriz Garcia-Rodriguez; Silvia Espina; Izaskun Arenaz; Jose M. Arbones-Mainar (Journal of Physiology and Biochemistry, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

Activated carbon as catalyst for microwave-assisted wet peroxide oxidation of aromatic hydrocarbons - Alicia L. Garcia-Costa; Lucia Lopez-Perela; Xiyan Xu; Juan A. Zazo; Juan J. Rodriguez; Jose A. Casas (Environmental Science and Pollution Research, 2018)

Bidirectional Neural Interaction Between Central Dopaminergic and Gut Lesions in Parkinson’s Disease Models - Pablo Garrido-Gil; Ana I. Rodriguez-Perez; Antonio Dominguez-Meijide; Maria J. Guerra; Jose L. Labandeira-Garcia (Molecular Neurobiology, 2018)

Antidiabetic Polypill Improves Central Pathology and Cognitive Impairment in a Mixed Model of Alzheimer’s Disease and Type 2 Diabetes - Carmen Infante-Garcia; Juan Jose Ramos-Rodriguez; Carmen Hierro-Bujalance; Esperanza Ortegon; Eleanor Pickett; Rosemary Jackson; Fernando Hernandez-Pacho; Tara Spires-Jones; Monica Garcia-Alloza (Molecular Neurobiology, 2018)

Cognitive Impairment and Brain and Peripheral Alterations in a Murine Model of Intraventricular Hemorrhage in the Preterm Newborn - Antonio Segado-Arenas; Carmen Infante-Garcia; Isabel Benavente-Fernandez; Daniel Sanchez-Sotano; Juan Jose Ramos-Rodriguez; Almudena Alonso-Ojembarrena; Simon Lubian-Lopez; Monica Garcia-Alloza (Molecular Neurobiology, 2018)

Novel Formulation Strategy to Improve the Feasibility of Amifostine Administration - Kavitha Ranganathan; Eric Simon; Jeremy Lynn; Alicia Snider; Yu Zhang; Noah Nelson; Alexis Donneys; Jose Rodriguez; Lauren Buchman; Dawn Reyna; Elke Lipka; Steven R. Buchman (Pharmaceutical Research, 2018)

Specific Energy Requirements in Electrokinetic Remediation - Maria Villen-Guzman; Cesar Gomez-Lahoz; Francisco Garcia-Herruzo; Carlos Vereda-Alonso; Juan M. Paz-Garcia; Jose M. Rodriguez-Maroto (Transport in Porous Media, 2018)

Fast versus slow growing tuna species: age, growth, and implications for population dynamics and fisheries management - Hilario Murua; Enrique Rodriguez-Marin; John D. Neilson; Jessica H. Farley; María Jose Juan-Jordá (Reviews in Fish Biology and Fisheries, 2017)

Ocular flutter following Zika virus infection - Emely Karam; Jose Giraldo; Flor Rodriguez; Carlos E. Hernandez-Pereira; Alfonso J. Rodriguez-Morales; Gabriela M. Blohm; Alberto E. Paniz-Mondolfi (Journal of NeuroVirology, 2017)

Influence of dissolved organic matter and oil on the biosorption of BTEX by macroalgae in single and multi-solute systems - Mayra Cecilia Rodriguez-Hernandez; Carlos E. Flores-Chaparro; Jose Rene Rangel-Mendez (Environmental Science and Pollution Research, 2017)

An overview on the application of advanced oxidation processes for the removal of naphthenic acids from water - Xiyan Xu; Gema Pliego; Juan A. Zazo; Shibo Sun; Patricia García-Muñoz; Li He; Jose A. Casas; Juan J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2017)

Long-Term Mangiferin Extract Treatment Improves Central Pathology and Cognitive Deficits in APP/PS1 Mice - Carmen Infante-Garcia; Juan Jose Ramos-Rodriguez; Irene Delgado-Olmos; Carlos Gamero-Carrasco; Maria Teresa Fernandez-Ponce; Lourdes Casas; Casimiro Mantell; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Expression of angiotensinogen and receptors for angiotensin and prorenin in the rat and monkey striatal neurons and glial cells - Pablo Garrido-Gil; Ana I. Rodriguez-Perez; Patricia Fernandez-Rodriguez; Jose L. Lanciego; Jose L. Labandeira-Garcia (Brain Structure and Function, 2017)

Progressive Neuronal Pathology and Synaptic Loss Induced by Prediabetes and Type 2 Diabetes in a Mouse Model of Alzheimer’s Disease - Juan Jose Ramos-Rodriguez; Tara Spires-Jones; Amy M. Pooler; Alfonso Maria Lechuga-Sancho; Brian J. Bacskai; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Gas1 expression in parietal cells of Bowman’s capsule in experimental diabetic nephropathy - Brenda I. Luna-Antonio; Rafael Rodriguez-Muñoz; Carmen Namorado-Tonix; Paula Vergara; Jose Segovia; Jose L. Reyes (Histochemistry and Cell Biology, 2017)

Thrombotic thrombocytopenic purpura in a new onset lupus patient? - Nery Sablón González; Noel Lorenzo; Yanet Parodis; Maria Belen Alonso Ortiz; Melek Kechida; Jose Carlos Rodriguez Perez (Immunologic Research, 2017)

Could the obligation to land undersized individuals increase the black market for juveniles: evidence from the Mediterranean? - Jose M Bellido; Mariano García‐Rodriguez; Teresa García‐Jiménez; María González‐Aguilar; Ana Carbonell‐Quetglas (Fish and Fisheries, 2017)
The latest Green Paper on the EU Common Fisheries Policy ( CFP ) identified the high level of discards in Europe as one of the structural weaknesses of the current CFP . The new CFP introduces a discard ban in European waters, with an obligation to land all regulated species. The fishing management system in the Mediterranean is based on effort control and technical measures, and this is raising some particular concerns about the effective implementation of the discard ban. With the exception of bluefin tuna ( Thunnus thynnus, Scombridae), there are no quotas in the Mediterranean and this regulation affects all regulated species with the minimum landing size. Under these circumstances, the discard ban may lead to an increase in the amount of juvenile fish caught, because such catches are not counted against a given quota, as is the case in the Atlantic fisheries, and thus, there is no incentive to avoid catching them. On the contrary, the obligation to land the juveniles that are now discarded and their subsequent fishmeal processing might even become commercially interesting. One possible consequence of the new regulation may be an increase in the illegal marketing of fish below the minimum size. The landing, storage and transportation of juveniles will all be legal, and this may simplify their commercialization via the black market. The discard ban and landing obligation should be accompanied by other measures to ensure their successful implementation, including the agreement of the fishing sector to comply with the rules and regulations.

Improving the Fenton process by visible LED irradiation - Gema Pliego; Patricia Garcia-Muñoz; Juan A. Zazo; Jose A. Casas; J.J. Rodriguez (Environmental Science and Pollution Research, 2016)

Genomic prediction for grain zinc and iron concentrations in spring wheat - Govindan Velu; Jose Crossa; Ravi P. Singh; Yuanfeng Hao; Susanne Dreisigacker; Paulino Perez-Rodriguez; Arun K. Joshi; Ravish Chatrath; Vikas Gupta; Arun Balasubramaniam; Chhavi Tiwari; Vinod K. Mishra; et al. (Theoretical and Applied Genetics, 2016)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Trends in the Intensification of the Fenton Process for Wastewater Treatment: An Overview - Gema Pliego; Juan A. Zazo; Patricia Garcia-Muñoz; Macarena Munoz; Jose A. Casas; Juan J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2015)

Analysis of In Vitro Aptamer Selection Parameters - Maureen McKeague; Erin M. McConnell; Jose Cruz-Toledo; Elyse D. Bernard; Amanda Pach; Emily Mastronardi; Xueru Zhang; Michael Beking; Tariq Francis; Amanda Giamberardino; Ashley Cabecinha; Annamaria Ruscito; et al. (Journal of Molecular Evolution, 2015)

On the Impact of Intraluminal Thrombus Mechanical Behavior in AAA Passive Mechanics - Fabián Riveros; Giampaolo Martufi; T. Christian Gasser; Jose F. Rodriguez-Matas (Annals of Biomedical Engineering, 2015)

Maintaining Antioxidant Potential of Fresh Fruits and Vegetables After Harvest - Jose A. Villa-Rodriguez; H. Palafox-Carlos; Elhadi M. Yahia; J. Fernando Ayala-Zavala; Gustavo A. Gonzalez-Aguilar (Critical Reviews in Food Science and Nutrition, 2015)

CXCL10/XCL1 fusokine elicits in vitro and in vivo chemotaxis - Yessica E. Sanchez-Lugo; Jose J. Perez-Trujillo; Yolanda Gutierrez-Puente; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Maria J. Loera-Arias (Biotechnology Letters, 2015)

Transducin-like enhancer of split 3 (TLE3) in adipose tissue is increased in situations characterized by decreased PPARγ gene expression - Francisco José Ortega; Marta Serrano; Sergio Rodriguez-Cuenca; José María Moreno-Navarrete; María Gómez-Serrano; Mònica Sabater; Jose Ignacio Rodriguez-Hermosa; Gemma Xifra; Wifredo Ricart; Belén Peral; Antonio Vidal-Puig; José Manuel Fernández-Real (Journal of Molecular Medicine, 2015)

Primary cilia in the developing pig testis - Young Ou; Camila Dores; Jose-Rafael Rodriguez-Sosa; Frans A. van der Hoorn; Ina Dobrinski (Cell and Tissue Research, 2014)

Occurrence and Removal of Selected Pharmaceuticals and Personal Care Products in Three Wastewater-Treatment Plants - Jeong-Wook Kwon; Jose M. Rodriguez (Archives of Environmental Contamination and Toxicology, 2014)

FMLP-, thapsigargin-, and H2O2-evoked changes in intracellular free calcium concentration in lymphocytes and neutrophils of type 2 diabetic patients - Shanti S. Kappala; Javier Espino; Jose A. Pariente; Ana B. Rodriguez; Satyan Rajbhandari; Arati Iyengar; Keshore R. Bidasee; Jaipaul Singh (Molecular and Cellular Biochemistry, 2014)

Total arsenic in rice milk - Ron Shannon; Jose M. Rodriguez (Food Additives & Contaminants Part B-Surveillance, 2014)

Physically based evaluation of climate models over the Iberian Peninsula - Carmen Sánchez de Cos; Jose M. Sánchez-Laulhé; Carlos Jiménez-Alonso; Juan M. Sancho-Avila; Ernesto Rodriguez-Camino (Climate Dynamics, 2013)

A Pull-Back Algorithm to Determine the Unloaded Vascular Geometry in Anisotropic Hyperelastic AAA Passive Mechanics - Fabián Riveros; Santanu Chandra; Ender A. Finol; T. Christian Gasser; Jose F. Rodriguez (Annals of Biomedical Engineering, 2013)

Characterization of CCDC28B reveals its role in ciliogenesis and provides insight to understand its modifier effect on Bardet–Biedl syndrome - Magdalena Cardenas-Rodriguez; Daniel P. S. Osborn; Florencia Irigoín; Martín Graña; Héctor Romero; Philip L. Beales; Jose L. Badano (Human Genetics, 2013)

Use of transgenic GFP reporter strains of the nematode Caenorhabditis elegans to investigate the patterns of stress responses induced by pesticides and by organic extracts from agricultural soils - Charumathi Anbalagan; Ivan Lafayette; Melissa Antoniou-Kourounioti; Carmen Gutierrez; Jose Rodriguez Martin; Debapratim K. Chowdhuri; David I. De Pomerai (Ecotoxicology, 2013)

Civil nuclear power at risk of tsunamis - Joaquin Rodriguez-Vidal; Jose M. Rodriguez-Llanes; Debarati Guha-Sapir (Natural Hazards, 2012)

New polymorphisms in human MEF2C gene as potential modifier of hypertrophic cardiomyopathy - Cristina Alonso-Montes; Manuel Naves-Diaz; Jose Luis Fernandez-Martin; Julian Rodriguez-Reguero; Cesar Moris; Eliecer Coto; Jorge B. Cannata-Andia; Isabel Rodriguez (Molecular Biology Reports, 2012)

Transgenic nematodes as biosensors for metal stress in soil pore water samples - Charumathi Anbalagan; Ivan Lafayette; Melissa Antoniou-Kourounioti; Mainul Haque; John King; Bob Johnsen; David Baillie; Carmen Gutierrez; Jose A. Rodriguez Martin; David de Pomerai (Ecotoxicology, 2012)

Genetic and antigenic relationships of vesicular stomatitis viruses from South America - Steven J. Pauszek; Jose del C. Barrera; Tony Goldberg; Rossana Allende; Luis L. Rodriguez (Archives of Virology, 2011)

Using disaster footprints, population databases and GIS to overcome persistent problems for human impact assessment in flood events - Debarati Guha-Sapir; Jose M. Rodriguez-Llanes; Thomas Jakubicka (Natural Hazards, 2011)

Autophagy and lipids: tightening the knot - Jose Antonio Rodriguez-Navarro; Ana Maria Cuervo (Seminars in Immunopathology, 2010)

Recapture processes and biological inference in monitoring burrow-nesting seabirds - Ana Sanz-Aguilar; Giacomo Tavecchia; Eduardo Minguez; Bruno Massa; Fabio Lo Valvo; Gustavo A. Ballesteros; Gonzalo G. Barberá; Jose Francisco Amengual; Ana Rodriguez; Miguel McMinn; Daniel Oro (Journal of Ornithology, 2010)

The Holocene volcanic history of Gran Canaria island: implications for volcanic hazards - Alejandro Rodriguez‐Gonzalez; Jose L. Fernandez‐Turiel; Francisco J. Perez‐Torrado; Alex Hansen; Meritxell Aulinas; Juan C. Carracedo; Domingo Gimeno; Hervé Guillou; Raphaël Paris; Martine Paterne (Journal of Quaternary Science, 2009)
Previous published data, combined with our results of 13 new radiocarbon ages and extensive geological fieldwork, indicate that during the past 11 ka 24 monogenetic basaltic eruptions occurred in the north sector of Gran Canaria. These eruptions can be grouped into three periods of eruptive activity: 1900–3200 14 C a BP; 5700–6000 14 C a BP; and an older period represented by only one eruption, El Draguillo, dated at 10 610 ± 190 14 C a BP. Archaeological studies have shown that the more recent eruptions affected prehistoric human settlements on the island. Field studies demonstrate that the eruptions typically built strombolian cones (30–250 m in height) and associated relatively long lava flows (100–10 350 m in length); a few eruptions also produced tephra fall deposits. The total erupted volume of these eruptions is about 0.388 km 3 (46.1% as tephra fall, 41.8% as cinder cone deposits and 12.1% as lava flows). The relatively low eruption rate (∼0.04 km 3 ka −1 ) during the past 11 ka is consistent with Gran Canaria's stage of evolution in the regional volcano‐tectonic setting of the Canary Archipelago. The results of our study were used to construct a volcanic hazards map that clearly delimits two sectors in the NE sector of Gran Canaria, where potential future eruptions would pose a substantial risk for densely populated areas. Copyright © 2009 John Wiley & Sons, Ltd.

Methamphetamine Enhances HIV-1 Infectivity in Monocyte Derived Dendritic Cells - Madhavan P. N. Nair; Zainulabedin M. Saiyed; Narayanan Nair; Nimisha H. Gandhi; Jose W. Rodriguez; Nawal Boukli; Elias Provencio-Vasquez; Robert M. Malow; Maria Jose Miguez-Burbano (Journal of Neuroimmune Pharmacology, 2009)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Exploring the influence of shrubs on herbaceous communities in a Mediterranean climatic context of two spatial scales - Jaime Madrigal; Jose Antonio García-Rodriguez; Roberto Julian; Angel Puerto; Belen Fernández-Santos (Plant Ecology, 2008)

Role of muscle mass on sprint performance: gender differences? - Jorge Perez-Gomez; German Vicente Rodriguez; Ignacio Ara; Hugo Olmedillas; Javier Chavarren; Juan Jose González-Henriquez; Cecilia Dorado; José A. L. Calbet (European Journal of Applied Physiology, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

Modeling Methadone Pharmacokinetics in Rats in Presence of P-glycoprotein Inhibitor Valspodar - Ignacio Ortega; Monica Rodriguez; Elena Suarez; Juan Jose Perez-Ruixo; Rosario Calvo (Pharmaceutical Research, 2007)

FEEDING ECOLOGY OF THE MARINE OTTER ( LUTRA FELINA ) IN A ROCKY SEASHORE OF THE SOUTH OF CHILE - Gonzalo Medina‐Vogel; Claudio Delgado Rodriguez; P. Ricardo E. Alvarez; V. Jose Luis Bartheld (Marine Mammal Science, 2004)
A bstract The marine otter ( Lutra felina ) lives exclusively along exposed rocky shorelines on the South American Pacific coast from Peru (6°S), to Cape Horn, Chile (56°S), and Isla de los Estados, Argentina. L. felina diet and its relationship to prey availability and energy content was assessed by spraint and prey remains analysis, direct observation, and the use of crab pots and fish traps, at four sites on the Valdivian coast in the south of Chile, between June 1999 and June 2000. Based on spraints analysis, the diet was composed of 25 species; 52% (13/25) of the species identified were crustaceans, 40% (10/25) were fish, and 8% (2/25) were mollusks. Crustaceans were found in 78% of 475 spraints, 100% of 929 prey remains, and 90.8% of prey determined by direct observation, fish in 20% of spraints and 9.0% of prey determined by direct observation, and mollusks in 2% of spraints and 0.2% of prey determined by direct observation. Observed seasonal variation in prey availability was reflected in the otter diet. Fourteen prey species were trapped; 43% (6/14) were crustaceans and 57% (8/14) fish, crustaceans were 93% of 566 trapped individuals, fish 7%. L. felina showed opportunistic feeding behavior, selecting prey seasonally according to their availability rather than to their energy input.

Variability of photosynthetic pigments in the Colombian Pacific Ocean and its relationship with the wind field using ADEOS-I data - Efrain Rodriguez-Rubio; Jose Stuardo (Journal of Earth System Science, 2002)

Adenovirus vector-directed expression of the neurotrophin-3 receptor (TrkC) in mouse astrocytes - Nazario Rubio, Jose Abad-Rodriguez (Journal of NeuroVirology, 2001)

Synthesis and characterization of Sodium cis-dichlorochenodeoxycholylglycinato(O,N) platinum(II) – Cytostatic activity - Julio J. Criado; M.C. Garcia-Moreno; Rocio R. Macias; Jose J.G. Marin; Manuel Medarde; E. Rodriguez-Fernandez (BioMetals, 1999)

A novel germline mutation in exon 5 of the multiple endocrine neoplasia type 1 gene - A. Chico; Luis Gallart; Eugenia Mato; Carmen Mayoral; Jesus M. Martin-Campos; Lluís Catasús; Jose Rodriguez-Espinosa; Xavier Matías-Guiu; Francisco Blanco-Vaca; Alberto de Leiva (Journal of Molecular Medicine, 1998)

Raptors as Indicators of Environmental Change in the Scrub Habitat of Baja California Sur, Mexico - Ricardo Rodriguez-Estrella; Jose Antonio Donazar; Fernando Hiraldo (Conservation Biology, 1998)

Identification, expression and tissue distribution of cytidine 5′-monophosphate N-acetylneuraminic acid synthetase activity in the rat - Beatriz Revilla-Nuin; Angel Reglero; Jose C Feo; Leandro B Rodriguez-Aparicio; Miguel A Ferrero (Glycoconjugate Journal, 1998)

The structure of carbonyl horseradish peroxidase: spectroscopic and kinetic characterization of the carbon monoxide complexes of His-42 → Leu and Arg-38 → Leu mutants - Jose Neptuno Rodriguez-Lopez; Simon J. George; R. N. F. Thorneley (JBIC Journal of Biological Inorganic Chemistry, 1998)

Human acetylator genotype: Relationship to colorectal cancer incidence and arylamine N-acetyltransferase expression in colon cytosol - Jose W. Rodriguez; Ward G. Kirlin; Ronald J. Ferguson; Mark A. Doll; Kevin Gray; Timothy D. Rustan; Mark E. Lee; Katherine Kemp; Paul Urso; David W. Hein (Archives of Toxicology, 1993)